Ethnobotany of Balimo (Zanthoxylum nitidum) in the Kanayatn Dayak Community in Tapakng, West Kalimantan - Letus Sepsamli; Jumari Jumari; Erma Prihastanti (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
The Kanayatn Dayak in Tapakng Village has a local culture of using balimo plants for traditional medicine. Balimo is a plant, it has an important meaning in traditional medicine by the Kanayatn Dayak community in Tapakng Village. This study aimed to examine the ethnobotanical knowledge of balimo plants and their advantage among the Kanayatn Dayak Â community in Tapakng Village. The research method with observation and deep interview and also semi-structured interview. Deep interviews was conducted with four key informants and the semi-structured interview was conducted with 60 respondents. The results showed that, the local people had a traditional treatment system to solve the disease problems. Balimo plants are used as a prevention of alcohol intoxication due to drinking arak and treatment of coughs (dry cough and bloody cough or (hemoptysis). The use of balimo as a prevention of intoxication has an important role because it is related to the Dayak Indigenous rituals. The level of ethnobotanical knowledge of local people showed that, 100% have heard about the balimo, 92% have seen balimo, and 55% have used it. This research provided information to the public about balimo that can be used in medication. Information on the utilization of balimo gives awareness to the people, the population of balimo really needs to be maintained in nature from extinction.